2020
DOI: 10.1111/ssqu.12792
|View full text |Cite
|
Sign up to set email alerts
|

Marvel, DC, and Sport: Investigating Rivalry in the Sport and Comic Settings

Abstract: Objective. The current article empirically investigated differences in fandom and rivalry between fans of a sport team and fans of the Marvel or DC comic brands. Methods. An online survey was distributed to fans of a sport team and/or the comic genre to measure how fans identified with their favorite brands (both sport and comics), and how they felt toward their rival brands. Results. Results illustrated that sport fans reported higher identification with their favorite teams than did fans of Marvel or DC towa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…The difference in opinion was likely due to differences in the ability to form judgments about comics and their form (La Cour, 2022). Studies have shown that even within the same age range, men and women and men had different judgments and views about comics (Havard, 2020). However, other studies have found no gender differences in attitudes toward comics (Crăciun, 2019).…”
Section: Resultsmentioning
confidence: 95%
“…The difference in opinion was likely due to differences in the ability to form judgments about comics and their form (La Cour, 2022). Studies have shown that even within the same age range, men and women and men had different judgments and views about comics (Havard, 2020). However, other studies have found no gender differences in attitudes toward comics (Crăciun, 2019).…”
Section: Resultsmentioning
confidence: 95%
“…We included only one study which focused on rivalries in popular culture. However, a new line of research focuses on rivalry in this field, for example, between Disney and Universal Studios fans (Havard et al, 2021) or between Marvel and DC comics brands fans (Havard et al, 2020b). Although initial findings indicate that these rivalries are less intense than sports rivalries, expanding rivalry research to other domains may have some critical theoretical implications since the antecedents for this sort of rivalry, such as past competitive interactions, are somewhat different from a "traditional" rivalry.…”
Section: Future Directionsmentioning
confidence: 99%